Devivir e tempo segundo João Duns Escoto - Parcerías, Pedro (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2005)

(untitled)
In what way is it possible to consider time in a thought that refuses any quidditative pertinence to the concept of measurement, to the concept of undividable and, consequently, to the concept of now, in the same way that it refuses all and any thesis that proceeds from existence? Working on the inner part of the unsettled questions of these apparently scotistic contradictions is the purpose of this article.